MOBILISASI BANGSA INDONESIA PADA MASA PENDUDUKAN JEPANGUNTUK KEPENTINGAN PERANG ASIA TIMUR RAYA TAHUN 1942-1945 - JEFRI RIESKI TRIYANTO (Universitas Negeri Yogyakarta, 2021)
Greater East Asia War is a continuation of World War II in Europe. Japan's ambition to dominate the region in Southeast Asia accordance with the ideology of the highway east asia co-prosperity and spirit Hakko i chiu. Japan to attack the strongest fleet in the Pacific of the United States on 8 December 1941. This war is called a war of the Pacific or Greater East Asia. The victory of the war turned out to be reciprocated by the United States since middle of 1942. The situation makes Japan to mobilize the people of Indonesia and other occupied areas for the benefit of war. Mobilization policies implemented in the political, economic and social mobilization of the masses. Japan also control in the fields of education, culture, and mass media. The policy aims to mobilize the people of Indonesia in all fields so that the Japanese get backup power if United States invade Indonesia. Keyword: Mobilization, Greater East Asia War, Japanese occupation